Pengaruh Atmosfer, Kualitas Produk dan Kualitas Layanan Terhadap Kepuasan Pelanggan Minuman Kopi pada Kedai “Kopi Dari Hati” di Kabupaten Bogor - Lorenza, Uyung; Susilowati, Isnurrini Hidayat; Marginingsih, Ratnawaty; Widiyanti, Wiwik (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2025)
The development of business types in Indonesia is increasing, marked by the emergence of many new types of businesses, one of which is the culinary business. This situation has led to intense competition among business actors. The purpose of this study is to see the influence of atmosphere, product quality, and service quality on customer satisfaction with coffee drinks at the "Kopi Dari Hati" shop in Bogor Regency. Quantitative methods are used for data collection with observation, questionnaires, documentation, and interviews. This study uses a non-probability sampling technique with a convenience sampling method on 155 respondents whose validity and reliability have been tested. The results of this study show that the atmosphere does not have a partial significant effect of -0.363 < t table with sig. 0.717 on customer satisfaction, product quality has a partial significant effect of 5.422 > t table with sig. 0.000 on customer satisfaction and service quality does not have a partial significant effect of 1.809 < t table with sig. 0.072 on customer satisfaction. Simultaneously, atmosphere, product quality, and service quality have a positive and significant effect of 27.462 > f table with sig. 0.000 < 0.05 on customer satisfaction.